A data-driven learning experiment in the legal English classroom using the FLAX platform - Marín Pérez, María José; Orts Llopis, María Ángeles; Fitzgerald, Alannah (Miscelánea: A Journal of English and American Studies, 2017)
This research presents a data-driven experiment in the legal English field where the FLAX, an open-source self-learning online platform, is assessed as regards its efficacy in aiding a group of legal English non-native undergraduates (divided into an experimental and a control group) to use legal terminology more consistently, amongst other language items. The experimental group were instructed to only resort to the FLAX and to exploit all the functionalities offered by it. Conversely, the control group could access any information source at hand except for the learning platform for the completion of the same task. Two learner corpora were gathered and analysed on a lexical and pragmatic level for the evaluation of term usage and distribution, lexical diversity, lexical fundamentality and the use of discourse markers. The results display a tendency on the part of the experimental group towards a more consistent usage of legal terminology, which also appears to be better distributed than the terms in the non-FLAX corpus. In contrast and on average, the lexicon in the FLAX-based corpus tends to be slightly more basic. Concerning the use of MD markers, the experimental group appears to use, though marginally, a greater number of evidentials, endophoric and interactional markers.